Selective extraction of cobalt ions through polymer inclusion membrane containing Aliquat 336 as a carrier. Issue 10 (25th February 2016) - Yıldız, Yasemin; Manzak, Aynur; Tutkun, Osman
Abstract: This study reports the selective separation of Co (II) from mixtures of cobalt and nickel solutions using cellulose tri-acetate (CTA)-based polymer inclusion membranes, which incorporated the commercial extractant trioctylmethylammonium chloride (Aliquat 336). Tributylphosphate (TBP) was used as a modifier, and 2- nitro phenyl pentyl ether (2-NPPE) was applied as the plasticiser to prepare the membranes. Several important transport parameters such as the plasticiser concentration, carrier type, carrier concentration, pH of acid, stirring speed, stripping solution type and concentration, complexing reagent (NH4 SCN) concentration and synergistic effect of the modifier were discussed. At the optimum conditions, following results were found: plasticiser concentration 0.2 mL, feed solution pH 4, feed phase stirring speed 900 rpm, stripping solution 1 M NH3  + 1 M TEA, complexing reagent (NH4 SCN) concentration 0.5 M and modifier TBP 25% w/w. Effective extraction was carried out under these conditions. The recovery factor of the cobalt ions was 100% for 4 h.